2018
DOI: 10.1038/s12276-018-0125-y
|View full text |Cite
|
Sign up to set email alerts
|

CircularRNA_104670 plays a critical role in intervertebral disc degeneration by functioning as a ceRNA

Abstract: This study was carried out to explore the roles of circular RNAs (circRNAs) in nucleus pulposus (NP) tissues in intervertebral disc degeneration (IDD). Differentially expressed circRNAs in IDD and normal NP tissues were identified based on the results of microarray analysis. Bioinformatics techniques were employed to predict the direct interactions of selected circRNAs, microRNAs (miR), and mRNAs. CircRNA_104670 was selected as the target circRNA due to its large multiplier expression in IDD tissues. After luc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(101 citation statements)
references
References 44 publications
1
100
0
Order By: Relevance
“…Several studies have confirmed that circRNAs are rich in miRNA binding sites and act as miRNA sponges to abolish the inhibition of miRNAs on their target genes in a mechanism called the competitive endogenous RNA (ceRNA) 24,25 . Increasing evidence indicates that circRNAs act as miRNA inhibitors in the development and progression of IVDD 18,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have confirmed that circRNAs are rich in miRNA binding sites and act as miRNA sponges to abolish the inhibition of miRNAs on their target genes in a mechanism called the competitive endogenous RNA (ceRNA) 24,25 . Increasing evidence indicates that circRNAs act as miRNA inhibitors in the development and progression of IVDD 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, cell metabolism, differentiation, proliferation, and survival involving these targeted mRNAs will be affected due to the biding of circRNAs and miRNAs 17 . Increasing evidence suggests the role of circRNAs in the pathogenesis of IVDD 18,19 . This study aimed to investigate the role of circRNAs in the pathogenesis of IVDD, and we selected circERCC2 based on bioinformatics analysis and explored its role in the regulation of mitophagy and apoptosis during the progression of IVDD.…”
Section: Introductionmentioning
confidence: 99%
“…These results revealed that circFMN2 may act as a biomarker and therapeutic target for CRC. Increasing evidence shows that circRNAs have a range of functions including regulation of RNA binding proteins (RBPs), promotion of mRNA transcription in cis and post-transcriptional regulation through sponging of miRNAs [26][27][28]. MiRNAs are a class of non-coding small RNAs of approximately 19-23 nucleotides in length, which are widely involved in various biological behaviors of cancer cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…Song et al performed circRNA microarray and identified circRNA_104670 as one of the highest upregulated circRNAs in degenerative NP tissues. Bioinformatic reconstruction of the regulatory network of circRNA_104670 revealed that this circRNA might act through the miR‐17‐3p‐matrix metallopeptidase (MMP)‐2 axis in NP cells.…”
Section: Functional Roles Of Specific Circrnas In Iddmentioning
confidence: 99%